Design and synthesis of conductive carbon polyhedrons enriched with Mn-Oxide active-centres for oxygen reduction reaction. (10th May 2018) - Ahmad Shah, Syed Shoaib; Najam, Tayyaba; Cheng, Chao; Chen, Siguo; Xiang, Rui; Peng, Lishan; Lu, Lijuan; Ding, Wei; Wei, Zidong
Abstract: The development of efficient, low-cost and stable electrocatalysts as the alternative to platinum for the oxygen reduction reaction (ORR) is of significance for many important electrochemical devices, such as fuel cells and metal–air batteries. Herein we discuss the design and synthesis of a Mnx Oy /N-C hybrid catalyst that can address both the activity and durability issues caused by the high productivity of peroxide (H2 O2 ) in nitrogen-doped carbon (N-C). The high activity and stability of the Mnx Oy /N-C-3 catalyst is ascribed to its novel hybrid structure, in which Mnx Oy is a good catalyst for decomposition of peroxide, while N-C not only catalyses the ORR but also prevents Mnx Oy agglomeration. RRDE study indicates a typical 4-electron ORR pathway with very low peroxide production (∼1.9%) and considerable stability. In light of the low cost and high earth abundance of Mn, the highly active Mnx Oy /N-C is a promising candidate to be used as a cathode material in metal–air batteries and alkaline fuel cells. Highlights: The mesoporous structures are well prepared by using Zn-MOF. Efficient and Facile synthetic Method. Low peroxide productivity and long stability. Well dispersed MnX Oy active centres on N-doped mesoporous carbon. A better strategy to avoid agglomeration of Mn-Oxide Particles.